Advances in GLP-1 receptor targeting radiolabeled agent development and prospective of theranostics - Velikyan, Irina (Theranostics, 2020)
In the light of theranostics/radiotheranostics and prospective of personalized medicine in diabetes and oncology, this review presents prior and current advances in the development of radiolabeled imaging and radiotherapeutic exendin-based agents targeting glucagon-like peptide-1 receptor. The review covers chemistry, preclinical, and clinical evaluation. Such critical aspects as structure-activity-relationship, stability, physiological potency, kidney uptake, and dosimetry are discussed.